Membranous glomerulopathy in women: clinical repercussions - Moreira França, João Antônio; Rodrigues Guedes, Sabrina; de Oliveira Cardoso, Lívia; Rodrigues Fernandes Duarte, Rodrigo; Augusto Santana Silva , Guilherme; Lacerda Ribeiro, Patrick; de Souza Martins, Gabriela; Arruda Prado Cavalcante, Thiago; Cardoso da Silva, Thamires Bárbara; Campos de Figueiredo Gonçalves, Ricardo; de Freitas Ribeiro, Gabriela; Keller Silva França, Vanny; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Membranous glomerulopathy is one of the most common causes of nephrotic syndrome in adults, with particular prevalence in women. This condition is characterized by thickening of the glomerular basement membrane, resulting in significant proteinuria and other clinical complications. The disease may have primary etiologies, such as the presence of antibodies against the phospholipase A2 receptor, or secondary to conditions such as infections, neoplasias and autoimmune diseases. In women, the clinical repercussions of membranous glomerulopathy may be more complex, since the interaction between hormones and immunological factors may influence the course of the disease and the response to treatment. Methodology: The research was conducted using the PRISMA checklist, with data collection from articles published in the last 10 years in the PubMed, SciELO and Web of Science databases. Five descriptors were used: "membranous glomerulopathy", "nephrotic syndrome", "women", "treatment" and "clinical implications". Inclusion criteria consisted of studies that addressed membranous glomerulopathy specifically in women, articles that presented clinical data, and peer-reviewed studies. Exclusion criteria included publications not related to the female population, articles with insufficient data, and non-original reviews. Results: The review revealed that membranous glomerulopathy in women is associated with a higher incidence of complications, including venous thrombosis and arterial hypertension. Treatments ranged from immunosuppressive to targeted therapies, with varied results in terms of remission and adverse effects. The quality of life of patients was significantly affected by the disease, highlighting the need for multidisciplinary management. Conclusion: Membranous glomerulopathy in women presents unique characteristics and clinical challenges, which demand special attention in diagnosis and treatment. Understanding the clinical repercussions and personalizing therapeutic approaches are essential to improve the quality of life of patients affected by this complex condition.